Princess test - Levine, Gail Carson; Elliott, Mark 1967-; Andersen, H. C. (Hans Christian), 1805-1875. (New York, NY HarperCollinsPublishers, 1999)
In this humorous retelling of Hans Christian Andersen's "The Princess and the Pea," Lorelei must pass many difficult tests in order to prove that she is a true princess and win the hand of Prince Nicholas.
"The princess tales."
Middle School.
Accelerated Reader AR
Reading Counts RC
115171
Keywords: Fairy tales; Juvenile Fiction -- Royalty; Juvenile Fiction -- Fairy Tales & Folklore -- General; Fairy tales